Speaking exams with less anxiety in Intelligent Computer-Assisted Language Assessment (ICALA): mirroring EFL learners’ foreign language anxiety, shyness, autonomy, and enjoyment - Elov, Botir; Abdullayeva, Irodakhon; Raupova, Laylo; Kholikov, Azam; Mirkasimova, Marguba (Language Testing in Asia, 2025)
A significant number of students experience anxiety when asked to speak in English. This unease, often rooted in factors such as shyness, lack of confidence, uncertainty, and a lack of motivation, can hinder their active participation during English oral exams. One of the most important goals that every English language teacher should strive to achieve is to assist pupils who are reticent in developing their self-confidence and improving their spoken English. Teachers can implement effective strategies in the classroom, particularly in online settings, to help hesitant students build confidence and speak English more comfortably. The research that is currently available on the subject of shyness and anxiety in students demonstrates that there is a significant gap in this area, and a critical examination is required. Consequently, the purpose of the current study was to investigate the impact of the implementation of Intelligent Computer-Assisted Language Assessment (ICALA) on EFL learners’ shyness, foreign language anxiety, autonomy, and enjoyment. Participants in this study were 65 students attending English language institutes in Tashkent, Uzbekistan. The results of the multivariate analysis of variance (MANOVA) indicate that applying ICALA in performing oral tests may moderate students’ shyness, foreign language anxiety, autonomy, and enjoyment in language assessment. This conclusion can be drawn from the findings of both aforementioned statistical methods. The ramifications of this investigation may be beneficial for individuals who are learning a language, those who are teaching language, and those who are making policy.